PP.26.25: RESISTANT ARTERIAL HYPERTENSION IN A PATIENT WITH ADRENAL INCIDENTALOMA, MULTIPLE STENO-OBSTRUCTIVE VASCULAR LESIONS AND ANTIPHOSPHOLIPID SYNDROME. (June 2015) - Marinelli, C.; Petramala, L.; Iannucci, G.; Gambale, G.; Concistre', A.; De Vincetis, G.; Zaccaria, A.; De Toma, G.; Letizia, C.
Abstract : Objective: Resistant arterial hypertension is defined as above of blood pressure (BP) > 140/90 mmHg despite therapy with three or more antihypertensive medications of different classes at maximum tolerable doses with one being diuretic. Design and method: An important consideration in defining a patient with resistant hypertension is the mislabeling of secondary hypertension as resistant hypertension. Secondary forms of arterial hypertension are not rare and are frequently associated with treatment resistance unless the etiological factor is removed. Here we report a 58 -year-old woman with resistant hypertension, BP of 220/110 mmHg on four anthypertensive drugs, post-prandial pain and left adrenal mass incidentally discovered. Results: The results of hormonal test revealed a subclinical Cushing's syndrome, and a renal ultrasonography, including Doppler, revealed that the longitudinal size of both kidney was different from each other (right 11 cm, left 7 cm) and the renal blood flow was decreased in the left kidney. An abdominal CT with arterial phase confirmed the left adrenal mass (30 x 20 mm of diameter) and revealed a thrombosis of the superior mesenteric artery, stenosis of left renal artery, and stenosis of common iliac artery. Extensive laboratory evaluation revealed positivity of lupus anticoagulant (LAC), and antiphospholipidic syndrome (APS) was posed. At different times before the patient underwent revascularization of the mesenteric and left renal arteries and then laparoscopic left adrenalectomy. Hystopathological examination consistent with a benign adrenocortical adenoma. At subsequent outpatient review, optimal BP was achieved (140/85 mmHg) with anthypertensive treatment, the glucocorticoid hormones were within normal range and a duplex ultrasound evidenced elevated velocities within the left renal artery. Conclusions: In conclusion, we report a patient with resistant hypertension caused by multiple steno-occlusive arteries due to APS and coesisting with subclinical Cushing syndrome.